Molecular Cloning and Gene Expression Analysis of the Phospholipase B Genes of Non-Albzcans Candzda Species - Cheang, Pey Shyuan (2005)
Phospholipase B (PLB) is known to be a virulence factor of Candida albicans. It hydrolyzes phospholipids and deranges constituents of host cell membranes which are likely to be involved in host cell invasion. The aims of the study are to clone and sequence the PLB genes of non-albicans Candida species and to assess the timedependent PLB gene expression of C. albicans, C. knrsei and C. tropicalis under the hyphal induction condition. Three pairs of degenerate primers designed from the conserved regions of PLBl genes of C. albicans, Saccharomyces cerevisiae and other hngi were used to amplifL DNA fragments of the PLB genes from C. krusei, C. parapsilosis and C. tropicalis by the polymerase chain reaction (PCR) approach. Arnplicons of approximately 5 10 bp were successfully obtained from the ATCC type strains of C. krusei, C. parapsilosis and C. tropicalis as well as a C. tropicalis clinical blood isolate, by using the first primer pair that targeted the 5' proximal end region of the putative PLB gene. The second and third pairs of degenerate primers amplified hgments corresponding to the 3' proximal end region of the putative PLB genes from the ATCC strains as well as clinical isolates of C. parapsilosis and C. tropicalis. These PCR products were cloned into E. coli vectors and subjected to DNA sequencing. The deduced amino acid sequences of these cloned partial open reading frames (ORFs) exhibited significant homology of about 60-70% identity with known fungal PLB genes. Sequence analysis showed that these putative PLB homologues and five other known PLBs are contained in a cluster of PLB family of proteins in which the amino acid sequences are more conserved towards the carboxyl terminus. Attempts to clone the hll length gene sequences of the non-albicans Candida using inverse PCR and RACE (Rapid Amplification of cDNA Ends) were futile. Using a simple phospholipase assay, varying levels of enzyme activity for the extracellular phospholipase was demonstrated in cultures of C. albicans, C. krusei, and C. tropicalis ATCC strains as well as C. parapsilosis and C. tropicalis clinical blood isolates. C. albicans produced significantly higher extracellular phospholipase relative to the other Candida species used in this study. C. glabrata and C. parapsilosis ATCC cultures showed undetectable extracellular phospholipase activity. In order to assess the PLB gene expression at mRNA level, semiquantitative RT-PCR approach was undertaken. The PLB gene expression time course analysis showed that there were significant differences in gene expression level over the 24 hours duration for cultures of C. albicans. Both the yeasts and hyphae forms expressed PLB gene at the mRNA level. PLB gene expression was undetectable in C. h e i , C. tropicalis ATCC and C. tropicalis clinical blood isolates in both the yeast and pseudohyphae forms. The results of this study strongly suggest that PLB is not a significant virulence determinant of non-albicans species. However, the data generated here would provide the vital groundwork for elucidating the instrinsic functional role of PLBs in the virulence and pathogenesis of the albicans and non-albicans Candida species.